In vivo interactions of continuous flucloxacillin infusion and high-dose oral rifampicin in the serum of 15 patients with bone and soft tissue infections due to Staphylococcus aureus - a methodological and pilot study - Garzoni, Christian (Springer International Publishing, 2014)
BACKGROUND: Increased antibiotic resistance against Staphylococcus aureus and low penetration into bone requires regimen optimization of available drugs. METHODS: We evaluate pharmoacokinetic and pharmacodynamic parameters (PK/PD) as well as in vivo interactions of continuous flucloxacillin 12 g/d administration combined with high dose oral rifampicin 600 mg bid in the serum of 15 adult patients with bone and soft tissue infections. We use the patient’s own serum directed against his own isolated S. aureus strain to reproduce in vivo conditions as closely as possible. RESULTS: The continuous flucloxacillin infusion constantly generated plasma free drug levels largely exceeding the serum minimal inhibitory concentrations (mean 74-fold). Combination with rifampicin significantly increased flucloxacillin levels by 44.5%. Such an increase following rifampicin introduction was documented in 10/15 patients, whereas a decrease was observed in 1/15 patients. Finally, all infections were cured and the combination was well tolerated. CONCLUSIONS: In this in vivo methodological pilot study among adult patients with orthopaedic infections due to S. aureus, we describe a new method and reveal substantial but inconsistent interactions between flucloxacillin and rifampicin, of which the clinical significance remains unclear.